Rebuilding Lives: A Conceptual Paper on Social Work Practice and Peer Support in the Recovery of Women with MDD - Idris, Afifah (Asian Social Work Journal, 2025)
This concept paper explores the synergistic role of social work practice and peer support in facilitating the recovery of women living with Major Depressive Disorder (MDD). Grounded in the CHIME Recovery Framework and Role Theory, the paper conceptualizes recovery as a holistic and empowering journey driven by personal agency, community integration, and psychosocial support. It highlights the unique vulnerabilities and psychosocial burdens faced by women, while advocating for recovery-oriented, peer-inclusive models of care that promote meaning, connection, and empowerment. The paper emphasizes the need to strengthen the role of social workers in Malaysia, through professional recognition, systemic support, and integration into community-based mental health services. By presenting a conceptual synthesis of theory, practice, and local context, this paper aims to guide policy development and future research in building inclusive and person-centered mental health recovery systems.